Obtenção das constantes cinéticas de agregação e ruptura de flocos obtidos a partir de água com cor elevada - Oliveira, Ricardo Fonseca de (2018)
Coagulation/flocculation is a process of great importance in the treatment of water for the public supply, being fundamental for the removal of the suspended particles. Determination of the coagulation pH x coagulant dosage pair and the knowledge of the size of the flakes are fundamental for a better flocculation efficiency and consequently of the treatment. In this sense, the present study sought to obtain the kinetic constants of aggregation and rupture through two different methodologies, using sodium aluminate as a coagulant in the treatment of water with high color (100 uH), simulated in Jartest bench equipment. The first stage of this work consisted of the construction of the coagulation diagram, with determination of the isoefficiency points in terms of the apparent color remaining in the water after sedimentation of the flakes. In the second stage of the work, the coagulation/flocculation processes, sedimentation, rupture and reflocculation of the flakes were simulated, followed by a system of acquisition and subsequent analysis of the flakes images, obtained by digital camera and laser light plane, for the construction of the curves of Particle Size Distribution (DTP) and obtaining its representative parameters. The DTP was distributed in 16 size classes, the first class being considered as representative of the primary particles. For floc formation, different values of mean velocity gradients (20, 30, 40 e 60 s-1) and for flocculation times of 5, 10, 20, 30, 40 and 60 minutes were investigated. For flakes fractions, the gradients of 100 and 200 s-1were used, and after the fracture, the flakes were submitted to reflocculation at the times of 5, 10, 20, 30, 40 and 60 minutes. The results were evaluated based on the kinetics of flocculation through the aggregation constants (KA) and rupture (KB) and DTP, using the mean diameter of the flakes as control parameter. For both the methodology using the first-class particle image analysis technique and the classical methodology, which considers the apparent color remaining for indirect measurement of flocculation efficiency, it was generally observed that, with the increase of the gradient, there was a decrease in the flocculation efficiency and that the tendency of equilibrium between KA e KB occurred in the first minutes of the process. In the tests of rupture and reflocculation, a tendency of formation of smaller flakes was observed. The KA e KB values found for the two methodologies are consistent with the values found in the literature.